The Effect of Brainwriting Learning Model Assisted by Short Film Media Bullying “RAPUH” on the Ability of Writing Response Texts of Grade VII Students of SMP Negeri 2 Percut Sei Tuan - Fika Salsabila Amar; Azhar Umar (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze whether there is an effect of using the Brainwriting model assisted by the short film media bullying